FEATURES OF THE DIAGNOSIS OF DIABETIC RETINOPATHY IN ADULTS - Abdurakhmonov Niyozbek Khamdamjon ogli (Scholar Express Journals, 2023)
Diabetic retinopathy (DR) is a serious complication of diabetes mellitus (DM), which, with progression, threatens with a significant decrease or complete loss of vision. It is the leading cause of blindness in the working-age population and, according to global estimates, occurs in every third patient with DM. DR has been studied for more than 160 years, and the introduction into clinical practice first of laser retinal coagulation in the 20th century, and then, in the 21st, of vascular endothelial growth factor (VEGF) inhibitors allowed to influence vascular proliferation in DR and reduce the risk of vision loss from diabetic macular edema (DMO). Nevertheless, these tools are only able to stop the progression of DR at the stages with complications with vision loss, and the main method of management for patients remains prevention – screening and influence on risk factors (hyperglycemia, hypertension, dyslipidemia). Currently, attention is being paid to possible new risk factors (physical inactivity, obesity, underweight, obstructive sleep apnea syndrome), the search is underway for early markers of DR on the fundus, which would allow more active influence on the pathological process in its early stages. This review is devoted to epidemiology, the history of study, proven and probable risk factors, modern and promising approaches to the prevention and treatment of DR, including accurate, less traumatic laser techniques (PASCAL, NAVILAS, D-MPL) and intravitreal antiangiogenic drugs studied in research.
Keywords: Diabetic retinopathy; diabetic macular edema; epidemiology; screening